Sidewalk flowers - Lawson, JonArno; Smith, Sydney, 1980- (Toronto ; Berkeley : Groundwood Books : House of Anansi Press, 2015)
A little girl collects wildflowers while on a walk with her distracted father. Each flower becomes a gift, and whether the gift is noticed or ignored, both giver and recipient are transformed by their encounter. This wordless picture book, conceived by award-winning poet JonArno Lawson and beautifully brought to life by illustrator Sydney Smith, is an ode to the importance of small things, small people and small gestures.
"Illustrations by Sydney Smith"--Page preceding title page.
Winner of the 2015 Governor General's Literary Award for children's literature (illustration), Canada Council for the Arts.
Issued also in electronic format.
Ages 4-7.
Charlotte Huck Recommended, 2016, National Council of Teachers of English
A Junior Library Guild selection
Keywords: Stories without words; Flowers -- Juvenile fiction; Father and child -- Juvenile fiction; Colors -- Juvenile fiction; Picture books for children; Stories without words; Graphic novels; Graphic novels